Examining the use behaviour of augmented reality technology through MARLcardio: adapting the UTAUT model / Nur Nabihah Mohd Nizar … [et al.] - Mohd Nizar, Nur Nabihah; Rahmat, Mohd Khairezan; Maaruf, Siti Zuraida; Damio, Siti Maftuhah (2018)
Augmented reality (AR) is one type of learning process that can be applied through mobile learning known as mobile augmented reality. AR offers an innovative learning space through an active interaction of superimposing digital contents into the real context to enhance learning experiences. Previous studies have found that AR in education is able to lead students to achieve higher levels of engagement in the learning process. In contrast, the potential of AR in education has not been explored intensively. Therefore, this article is to look into factors that might influence pre-service teachers use behaviour of Mobile Augmented Reality Learning Cardiovascular (MARLCardio). A self-designed MARLCardio app has been used as an experimental instrument in collecting data. The influencing factors towards use behaviour of MARLCardio are performance expectancy, effort expectancy, social influence and facilitating conditions. This study is a part of an on-going research. In this study, a total of 75 respondents used MARLCardio app before answering a survey questionnaire. The respondents were preservice teachers at one public university in Malaysia. All data from the questionnaire were analysed using multiple regression analysis. As a result of this investigation, findings showed that effort expectancy is the dominant factor in determining the use behaviour of MARLCardio. Interestingly, performance expectancy did not show any significant relationship.